(untitled) (Quinto Sol, 2011)
The article poses an inquiry about one of the main problems of syndical spectrum in Mendoza before the decisive political context of 1945: the high levels of fragmentation of its associations. Organized workers, judging the scene in different ways, tried to optimize their actions from different perspectives. Some labor federations struggled to unite syndicalism, but ideological differences caused the failure of the initiatives. The provincial unions who decided to support Perón after October 1945 were abruptly and artificially projected on a same path. This is partly the cause of their later relative weakness. The way in which Labor Party was designed showed, however, the strength of local criteria to configure a novel political organization. Even if political events determined unity, previous leaderships prevailed.